Supply Chain Management Strategies to Improve Distribution Efficiency - Nurhadida Nasution; Ramerson J Sumbayak (ITScience (Information Technology and Science), 2026)
This study aims to analyse Supply Chain Management strategies to improve the efficiency of local product distribution. The background of this study is based on the low efficiency of the distribution system, characterised by high logistics costs, long delivery times, and a lack of coordination between supply chain actors. This condition impacts the low competitiveness of products in the market. The research method used is a descriptive approach with a combination of qualitative and quantitative analysis. Data were obtained through interviews, observations, and questionnaires distributed to supply chain actors, including farmers, collectors, wholesalers, and retailers. Data analysis techniques used include descriptive analysis, distribution efficiency analysis, and SWOT (Strengths, Weaknesses, Opportunities, Threats) analysis. The results show that long and poorly integrated supply chains are the main causes of distribution inefficiency. In addition, limited infrastructure, low technology utilisation, and weak coordination between actors also worsen distribution performance. Strategies that can be implemented to improve distribution efficiency include supply chain integration, utilisation of digital technology, institutional strengthening, and improvement of logistics systems. In conclusion, effective and integrated supply chain management can improve distribution efficiency, reduce costs, and accelerate the flow of products to consumers. Therefore, support is needed from various parties, both business actors and the government, to optimise the supply chain system.